IFN‐γ and PPARδ influence the efficacy and retention of multipotent adult progenitor cells in graft vs host disease. (16th August 2021) - Carty, Fiona; Dunbar, Hazel; Hawthorne, Ian J.; Ting, Anthony E.; Stubblefield, Samantha R.; Van't Hof, Wouter; English, Karen
Abstract: Cell‐based therapy for the treatment of inflammatory disorders has focused on the application of mesenchymal stromal cells (MSCs) and multipotent adult progenitor cells (MAPCs). Despite the recent positive findings in industry‐sponsored clinical trials of MSCs and MAPCs for graft vs host disease (GvHD), cell therapy is efficacious in some but not all patients, highlighting the need to identify strategies to enhance cell‐based therapeutic efficacy. Here, we demonstrate the capacity for interferon (IFN)‐γ licensing to enhance human MAPC efficacy and retention following early administration in a humanized mouse model of acute GvHD (aGvHD). Activation of the nuclear receptor peroxisome proliferator‐activated receptor delta (PPARδ) negatively influenced the retention and efficacy of human MAPCs as well as IFN‐γ‐licensed MAPCs in the aGvHD model. PPARδ antagonism significantly enhanced the efficacy of human MAPCs when administered early in the humanized aGvHD model. COX‐2 expression in human MAPC was significantly decreased in IFN‐γ licensed MAPCs exposed to a PPARδ agonist. Importantly, MAPC exposure to the PPARδ antagonist in the presence of a COX‐2 inhibitor indomethacin before administration significantly reduced the efficacy of PPARδ antagonized MAPCs in the aGvHD humanized mouse model. This is the first study to demonstrate the importance of PPARδ in human MAPC efficacy in vivo and highlights the importance of understanding the disease microenvironment in which cell‐based therapies are to be administered. In particular, the presence of PPARδ ligands may negatively influence MAPC or MSC therapeutic efficacy. Abstract : Interferon‐γ (IFN‐γ) licensing enhances the therapeutic efficacy of human multipotent adult progenitor cells (MAPCs) in a mouse model of acute graft vs host disease (aGvHD). Activation of peroxisome proliferator‐activated receptor (PPAR) δ reduces, whereas antagonism of PPARδ(−) enhances MAPC efficacy in aGvHD. PPARδ agonism reduces COX‐2 expression in IFN‐γ licensed MAPC. Figure created with BioRender.com.